2005
DOI: 10.3310/hta9230
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review to examine the impact of psycho-educational interventions on health outcomes and costs in adults and children with difficult asthma

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 277 publications
(321 reference statements)
4
36
0
4
Order By: Relevance
“…These findings strongly indicate that both nurse-administered asthma education alone and nurseadministered asthma education plus pharmacist counseling result in increasing patients' knowledge about asthma, agreeing with previous studies of increased knowledge associated with asthma education [5,10,12,[14][15][16][17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings strongly indicate that both nurse-administered asthma education alone and nurseadministered asthma education plus pharmacist counseling result in increasing patients' knowledge about asthma, agreeing with previous studies of increased knowledge associated with asthma education [5,10,12,[14][15][16][17].…”
Section: Discussionsupporting
confidence: 90%
“…Self-efficacy, a sense of having control over events, has also been shown to improve self-management in adolescents [8] and adults [9] with asthma. Asthma education results in reduced emergency visits, reduced medication use during hospital stays [10][11][12][13], improved symptom scores [14,15], and improved inhalation techniques [3,16]. Research on the effect of patient education on knowledge and healthrelated quality of life (HRQOL) has shown benefits of asthma education and self-management as recommended by GINA guidelines [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Again in the group with need of ICS at inclusion education showed a more pronounced effect on emergency visits in the whole group: the OR for need of an emergency visit in the training versus the education group were 3.99 versus 2.02 (Table 6). This observation is in line with metaanalyses on education in difficult asthma [14] or severe asthma (indicated by a hospitalization) [3] where it was easier to show an effect of education than in asthma in general [2].…”
Section: Discussionsupporting
confidence: 84%
“…A closer look on the interventions described in the meta-analysis proved them to be most similar to what was given as an instruction in our study. In a systematic review on the effectiveness of psycho-educational interventions on health outcomes in children with difficult asthma, the authors also found that psycho-education in comparison with standard asthma training reduces the number of hospitalizations [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation